(3GdhSjW (B:s (3aj GdOQGSGJ GdLGeYjI(B((3GdLRA GdGhd(B) /s - (3Hf NQa Gddg, GdWGgQs ((3GdLRGFQ (B:s (3OGQ gheg ddWHGYI h GdfTQ ,s, 2002)
(3JGJj gPg GdSdSdI GdYdejI GdeJNUUI aj GdebQQGJ GdLGeYjI ceSGgeI ef WQa fNHI ef GdGSGJPI GdLGeYjjf aj JZWjI LGfHG ef GdfbU aj GdeQGLY GdPj JYGfj efg GdecJHGJ h Pdc aj eMGhdI dJYhjV gPG GdfbU Yf WQjb hVY ehGO HYV GdebQQGJ h GdHQGeL GdOQGSjI aj eJfGhd GdWGdH GdLGeYj HUaI NGUI h cd GdHGMKjf GdegJejf s
Keywords: (3GdJShjb GdSjGSjs; (3GdUMGaI GdecJhHs; (3hSGFd GdEYdGes; (3OQGSI GdLeghQs